Comparison of HS-SDME with SPME and SPE for the determination of eight organochlorine and organophosphorus pesticide residues in food matrices - Kin C.M.; Huat T.G. (Preston Publications, 2023)
A headspace single-drop microextraction (HS-SDME) procedure is optimized for the analysis of organochlorine and organophosphorous pesticide residues in food matrices, namely cucumbers and strawberries by gas chromatography with an electron capture detector. The parameters affecting the HS-SDME performance, such as selection of the extraction solvent, solvent drop volume, extraction time, temperature, stirring rate, and ionic strength, were studied and optimized. Extraction was achieved by exposing 1.5 ?L toluene drop to the headspace of a 5 mL aqueous solution in a 15-mL vial and stirred at 800 rpm. The analytical parameters, such as linearity, correlation coefficients, precision, limits of detection (LOD), limits of quantification (LOQ), and recovery, were compared with those obtained from headspace solid-phase microextraction (HS-SPME) and solid-phase extraction. The mean recoveries for all three methods were all above 70% and below 104%. HS-SPME was the best method with the lowest LOD and LOQ values. Overall, the proposed HS-SDME method is acceptable in the analysis of pesticide residues in food matrices.